Digital Learning Fatigue and Academic Motivation in Students at Ahmad Dahlan University Yogyakarta - Masduki, Yusron; Johari, Mohd Erfino (Universitas Muhammadiyah Magelang, 2025)
Digital learning environments have become an integral part of higher education; however, prolonged exposure to online platforms and digital devices increases the risk of digital learning fatigue among university students. This study investigates the effects of digital learning fatigue on academic motivation and learning engagement among undergraduate students at Ahmad Dahlan University, Yogyakarta. Employing a quantitative explanatory design, data were collected from 300 students and analyzed using Structural Equation Modeling”“Partial Least Squares (SEM-PLS). Three latent variables were examined: Digital Learning Fatigue (DLF), Academic Motivation (AM), and Learning Engagement (LE). The measurement model demonstrated strong convergent and discriminant validity, with high composite reliability across all constructs. Structural model analysis revealed that digital learning fatigue had a significant negative effect on academic motivation (Î² = ”“0.41, p < 0.001), while academic motivation had a strong positive effect on learning engagement (Î² = 0.58, p < 0.001). The direct effect of digital learning fatigue on learning engagement was negative but not statistically significant (Î² = ”“0.12, p = 0.060). Mediation analysis confirmed a significant indirect effect of digital learning fatigue on learning engagement through academic motivation (Î² = ”“0.24, p < 0.001), indicating full mediation. These findings suggest that students”™ learning engagement declines not directly due to digital fatigue, but because fatigue undermines their academic motivation. The study highlights the central role of motivational processes in sustaining student engagement within digital learning contexts and offers implications for designing supportive and sustainable online learning environments in higher education.